KAJIAN YURIDIS TERHADAP SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN KEDUA (II) DAN BERIKUTNYA SEBAGAI PERPANJANGAN SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN PERTAMA (I) YANG TELAH BERAKHIR JANGKA WAKTU - MUHAMMAD IQBAL (PREMISE LAW JURNAL, 2016)
The use of SKMHT (The Power of Attorney to Grant a Morlgage) by the Creditor to the Debtor is motivated by some reasons, such as the collateral is outside the authority of the Notary/PPAT (Official Land Deed Registrar), it is in the application process at BPN (National Land Agency) (for example Release, Title Transfer, Mortgage Right, Merger, or Certtficate Application), and the Debtor cannot attend by the time of the signing of Mortgage Loan Deed. The legal position of tlrc second SKMHT (II) and lureinofier refer to the extension of the first SKMHT (I) which has been expired was that it should be signed before a Notary and PPAT attended by witnesses and numbered and dated according to when the SKMHT was signed by the parties as regalated in UUJN and PJN. The legal efforts made by the Creditor over the Debtor's "Bad Credit" who did not want to sign the extension of SKMHT consisted of 3 ways, namely by applying forMediation, A Claim to the District Court, and filing to the Commercial Court. The sanction to the Notary who hod made the SKMHT which was not in line with the provisions in UUJN besides Compensation, indemnity, and the interest to the Notnry as the injured party can also be sentenced as stipulaed in Article 1,7 pagraph (11) of UUJN. Keywords: SKMHT (The Power of Attorney to Grant a Mortgage)